Synthesis of an Activatable Tetra-Substituted Nickel Phthalocyanines-4(3H)-quinazolinone Conjugate and Its Antibacterial Activity - Asma M. Elsharif; Tamer E. Youssef; Suhailah S. Al-Jameel; Hanan H. Mohamed; Mohammad Azam Ansari; Suriya Rehman; Sultan Akhtar (Advances in Pharmacological Sciences)
The aim of this study was to synthesize a series of nickel(II)phthalocyanines (NiPcs) bearing four 4(3H)-quinazolinone ring system units, (qz)4NiPcs 4a–d. The electronic factors in the 4(3H)-quinazolinone moiety that attached to the NiPc skeleton had a magnificent effect on the antibacterial activity of the newly synthesized (qz)4NiPcs 4a–d against Escherichia coli. The minimum MICs and MBCs value were recorded for compounds 4a, 4b, 4c, and 4d, respectively. The results indicated that the studied (qz)4NiPcs 4a–d units possessed a broad spectrum of activity against Escherichia coli. Their antibacterial activities were found in the order of 4d > 4c > 4b > 4a against Escherichia coli, and the strongest antibacterial activity was achieved with compound 4d.